Pelatihan Pembuatan Empon-Empon Untuk Meningkatkan Daya Tahan Tubuh Dimasa Pandemi Covid-19, Di Desa Bantaran, Kabupaten Probolinggo - Widayanto, Mutinda Teguh; Koeshardjono, R. Hery; Hendra, Joni (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2022)
The Covid-19 outbreak has spread to almost of all the regions of the world and has affected various aspects of people lives. The economic, educational, and social sectors were not immune from the impact. Based on the results of research conducted, to be able to overcome these problems, there was one factor that could overcome impact of the virus attack was the existence of a good immune system. Empon-empon traditional drinks were known to contain various natural ingredients that are efficacious to enhance the body’s resistance of viral attacks. activity of socializing the produce of empon-empon aimed to provide an understanding the benefits of empon-empon in increasing endurance and to socialize the making it to the residents of Bantaran Village, Probolinggo Regency. This activity was hoped that the people would understand the benefit and be able to produce both for consumption to increase immunity and can be commercialized to increase household income.